Rapid detection of Mycoplasma pneumoniae by an assay based on PCR and probe hybridization in a nonradioactive microwell plate format. - Kessler, H H (1997)
A new molecular assay, based on a rapid DNA extraction protocol, PCR, and hybridization to a specific probe in a nonradioactive microwell plate format was used to detect Mycoplasma pneumoniae in bronchoalveolar fluid specimens. The sensitivity of the assay was determined to be 10 to 100 organisms with M. pneumoniae reference strains. Specificity testing with different bacteria capable of producing pneumonia showed no cross-reactivity. In a prospective study, bronchoalveolar lavage fluids obtained from patients with pneumonia were investigated with the PCR assay and compared to culture. Twelve positive samples were detected with the PCR assay. Seven of them were subsequently confirmed by culture. All patients with positive PCR results seroconverted. Application of the PCR assay described may lead to safe and early diagnosis of M. pneumoniae in patients with pneumonia.